Active Aβ immunotherapy CAD106 in Alzheimer's disease: A phase 2b study. Issue 1 (23rd December 2016) - Vandenberghe, Rik; Riviere, Marie‐Emmanuelle; Caputo, Angelika; Sovago, Judit; Maguire, R. Paul; Farlow, Martin; Marotta, Giovanni; Sanchez‐Valle, Raquel; Scheltens, Philip; Ryan, J. Michael; Graf, Ana
Abstract: Introduction: This randomized, double‐blind, placebo‐controlled, 90‐week study assessed safety, tolerability, and immunogenicity of CAD106 with/without adjuvant in patients with mild Alzheimer's disease. Methods: One hundred twenty‐one patients received up to seven intramuscular injections of CAD106 (150 μg or 450 μg) or placebo ± adjuvant over 60 weeks. An amyloid positron emission tomography (PET) substudy was also conducted. Results: CAD106 induced strong serological responses (amyloid‐beta [Aβ]–Immunoglobuline G[IgG]) in 55.1% (150 μg) and 81.1% (450 μg) of patients (strong serological responders [SSRs]). Serious adverse events (SAEs) were reported in 24.5% (95% confidence interval [CI] 16.7–33.8) of the patients in the active treatment group and in 6.7% (95% CI 0.2–31.9) in the placebo group. Three of the SAEs were classified as possibly related to study drug by the investigators. No evidence of central nervous system inflammation was found. Amyloid‐related imaging abnormalities (ARIAs) occurred in six cases, all of them were strong serological responders. None of the ARIAs were symptomatic. Serum Aβ‐IgG titer area under the curves correlated negatively with amyloid PET standardized uptake value ratio percentage change from baseline to week 78 within the CAD106‐treated patients (r = −0.84, P = .0004). Decrease in cortical gray‐matter volume from baseline to week 78 was larger in SSRs than in controls ( P = .0077). Discussion: Repeated CAD106 administration was generally well tolerated. CAD106 450 μg with alum adjuvant demonstrated the best balance between antibody response and tolerability.